2015
DOI: 10.1002/jemt.22606
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of silk fibroin carriers for controlled release

Abstract: Silk fibroin provides a new option for controlled release systems as a result of its excellent biodegradability, biocompatibility, and mechanical properties. As the core material, silk fibroin can be designed and widely used in drug/gene delivery, regenerative medicine, and other biomedical fields. This review focuses on the preparation methods, loading molecules, and applications of silk fibroin-based controlled release systems including microspheres, microcapsules, films, microparticles, microneedles, liposo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 94 publications
0
22
0
Order By: Relevance
“…To utilize the superior properties of silk stored in its molecular structures, nano‐level formulations of silk can be exploited using various routes. Nanoparticles of silk fibroin can be obtained through emulsion‐solvent evaporation, self‐assembly, phase separation, spray drying, rapid expansion of supercritical solution, electro‐gelation, salting out, and so on . The above procedures utilize reconstituted silk having random coil structures which needs to be reconverted to pleated structures; hence material properties are compromised .…”
Section: Introductionmentioning
confidence: 99%
“…To utilize the superior properties of silk stored in its molecular structures, nano‐level formulations of silk can be exploited using various routes. Nanoparticles of silk fibroin can be obtained through emulsion‐solvent evaporation, self‐assembly, phase separation, spray drying, rapid expansion of supercritical solution, electro‐gelation, salting out, and so on . The above procedures utilize reconstituted silk having random coil structures which needs to be reconverted to pleated structures; hence material properties are compromised .…”
Section: Introductionmentioning
confidence: 99%
“…Several research studies have shown the excellent characteristics of SFNs as a vehicle for drugs and biomolecules [38][39][40][41], so their production will presumably reach industrial scale in coming years. For this reason, it is of great interest to know all the parameters that affect the formation of nanoparticles to standardize the process and control their features.…”
Section: Introductionmentioning
confidence: 99%
“…Silk fibroin (SF), a fibrous protein extracted from silkworm cocoons, is being explored as a promising material for high‐performance wound dressings and controlled delivery systems . SF membranes are able to absorb wound exudate, becoming flexible dressings, and to adhere to the wound, preventing excessive flow of exudates, proteins, and substances that promote cell proliferation .…”
Section: Introductionmentioning
confidence: 99%